2016
DOI: 10.1186/s10194-016-0652-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 1 mg folic acid supplementation on clinical outcomes in female migraine with aura patients

Abstract: BackgroundMigraine is a common neurovascular condition that may be linked to hyperhomocysteinemia. We have previously provided evidence that reduction of homocysteine with a vitamin supplementation can reduce the occurrence of migraine in women. The current study examined the occurrence of migraine in response to vitamin supplementation with a lower dose of folic acid.MethodsThis was a 6 month randomised, double blinded placebo controlled trial of daily vitamin supplementation containing 1 mg of folic acid, 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 45 publications
1
39
0
1
Order By: Relevance
“…This effect was most pronounced in the C allele carriers of the MTHFR gene variant. Another study found that supplementation with a 1 mg dosage of folate and other B vitamins did not reduce headache outcome measures, which could indicate that high doses of folate acid are needed to see a clinical effect . Therefore, there may be certain subgroups of persons with migraine that might benefit from a high folate diet and/or supplements that contain moderate to high amounts of folate and vitamins B12 and B6.…”
Section: High Folate Dietsmentioning
confidence: 99%
“…This effect was most pronounced in the C allele carriers of the MTHFR gene variant. Another study found that supplementation with a 1 mg dosage of folate and other B vitamins did not reduce headache outcome measures, which could indicate that high doses of folate acid are needed to see a clinical effect . Therefore, there may be certain subgroups of persons with migraine that might benefit from a high folate diet and/or supplements that contain moderate to high amounts of folate and vitamins B12 and B6.…”
Section: High Folate Dietsmentioning
confidence: 99%
“…It was shown that MMA was remarkably higher in migraine patients than controls (mean values were 1.39 vs 1.01 µg/dL, respectively). [41][42][43][44][45] However, it has been suggested migraineurs might be at a higher risk for having a lower concentration of vitamin B12 due to higher prevalence of GI disorders and chronic NSAIDs consumption 17 that can impair intrinsic factor production and vitamin B12 absorption. 13,14 Consequently, vitamin B12 deficiency/insufficiency can cause dysfunction of methionine metabolism pathway that is highly dependent on appropriate concentrations of B12.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33] Furthermore, there is a considerable body of literature on decreased magnesium levels especially during ictal phases in migraine suffers when comparing to healthy individuals. [34][35][36] Moreover, it has been demonstrated that supplementation with vitamin B2, 37-40 B9, B6, [41][42][43][44][45] vitamin D, [46][47][48] and magnesium [49][50][51] could attenuate migraine features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It found no significant improvement in headache disability, frequency, or severity from baseline to completion of treatment compared with placebo using the Migraine Disability Assessment Score (MIDAS). 60 Butterbur, or Petasites hybridus, has a long and complex history of use in headache. Although butterbur reduces the frequency of headache in patients in RCTs, 61 50 An RCT in 60 patients with migraine with or without aura compared yoga practice five days a week for six weeks with conventional care control.…”
Section: Safetymentioning
confidence: 99%